PENATAAN INFRASTRUKTUR DRAINASE DI KOTA PEKANBARU - Pebri Ana. S; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Drainage is a series of buildings that serve water that serves to reduce or remove excess water from an area or land, so that the land can function optimally. In accordance with the regulations of the Minister of Public Works of the Republic of Indonesia Number 12 Year 2014 on the Implementation of the urban drainage system, which so far has not laid out well because there are many areas that are flooded when it rained. The purpose of this research was conducted to determine how the arrangement of drainage management in Dinas Pekerjaan Umum Perumahan Permukiman dan Cipta Karya and what factors are inhibiting the development of the current drainage.In explaining the arrangement of infrastructure management in Dinas Pekerjaan Umum Perumahan Permukiman dan Cipta Karya, researchers using the theory of G.R. Terry covering planning, organizing, implementing, monitoring. The researchers used a qualitative descriptive method. Data was collected through interviews, observation, literature (collection of documents).The results showed that the arrangement of drainage management from planning, organizing, implementing and monitoring is well defined. Already there are policies that govern the planning, organization, implementation, and supervision were already performing well, but there are several factors that inhibit the development of drainage, so there are still areas that are still flooded when it rains.Key Words : Management, Drainage, Dinas Pekerjaan Umum Perumahan Permukiman dan Cipta Karya